“IT’S NOT A PROBLEM TO BE GAY, THE PROBLEM IS TO BE GAY AND EMPLOYED” - THE MULTIPACT FORMS OF LGBTQIA+-PHOBIA IN THE WORK MARKET - Augusto Silva de Castro, Hudson; Descovi Schimith, Cristiano (Revista Gênero e Interdisciplinaridade, 2023)
According to Drydakis (2015), business characteristics negatively affect the performance of LGBTQIA+ in the labor market. These characteristics make it possible for LGBTQIA+-phobia to present itself in different ways, both in the pre-selection, as well as in the hiring, dismissal and post-dismissal of employees (MEDEIROS, 2007). Given these assumptions, the academic and social importance of describing the multifaceted ways in which LGBTQIA+-phobia is presented in the labor market and how LGBTQIA+ is affected by it is seen, which is the objective of this research. In order to carry out the research, we first sought to understand, in the existing literature, the difficulties encountered by LGBTQIA+ in the labor market, as well as the consequences of the prejudice suffered in their lives. To achieve the objective, interviews were made available virtually through a structured questionnaire with objective questions. The sample was selected using the non-statistical convenience method. In total, 54 (fifty-four) interviews were collected and 48 (forty-eight) were validated. In the interviews, it was observed that the LGBTQIA+ suffers from different types of prejudices in the labor market and that such prejudices negatively interfere with their productivity, efficiency and the achievement of their professional goals.